Pengembangan Sistem Promosi Digital Dengan OpenCart untuk Peningkatan Penjualan UMKM Produk Lokal di Solok Selatan - Maulida, Mia; Annas, Firdaus; Effendi, Chantika (Yayasan Lembaga Studi Makwa, 2023)
This study aims to develop a digital promotion system using OpenCart to increase sales of local products in South Solok. Currently, local product promotions are still carried out manually through direct marketing and word of mouth, as well as through social media such as Facebook and WhatsApp. However, this approach is less effective in reaching a wider market and lack of consumer awareness of local products. Therefore, a digital promotion system is needed to record MSME products in South Solok and provide wider access or opportunities and can develop sales sustainably. This study uses the Research and Development (R&D) method using the PPE development model with planning, production and evaluation stages. These results indicate that the OpenCart-based system is able to provide an effective solution in facilitating digital sales, expanding market reach and managing promotion effectiveness. The OpenCart system supports various features, such as product catalogs, online payment systems and social media integration. The main findings show an increase in market reach and efficiency of the marketing process which contributes to increasing sales of local products in South Solok, and is expected to be a model for the development of similar digital platforms in other areas to boost the local economy.